Guts Imbalance Imbalances the Brain: A Review of Gut Microbiota Association With Neurological and Psychiatric Disorders - Mitrea, Laura; Nemeş, Silvia-Amalia; Szabo, Katalin; Teleky, Bernadette-Emőke; Vodnar, Dan-Cristian (Frontiers in Medicine, 2022)
Over the last 10 years, there has been a growing interest in the relationship between gut microbiota, the brain, and neurologic-associated affections. As multiple preclinical and clinical research studies highlight gut microbiota’s potential to modulate the general state of health state, it goes without saying that gut microbiota plays a significant role in neurogenesis, mental and cognitive development, emotions, and behaviors, and in the progression of neuropsychiatric illnesses. Gut microbiota produces important biologic products that, through the gut-brain axis, are directly connected with the appearance and evolution of neurological and psychiatric disorders such as depression, anxiety, bipolar disorder, autism, schizophrenia, Parkinson’s disease, Alzheimer’s disease, dementia, multiple sclerosis, and epilepsy. This study reviews recent research on the link between gut microbiota and the brain, and microbiome’s role in shaping the development of the most common neurological and psychiatric illnesses. Moreover, special attention is paid to the use of probiotic formulations as a potential non-invasive therapeutic opportunity for prevention and management of neuropsychiatric-associated affections.